The Effect of Organizational Culture on Organizational Performance in Government Functional Audit Institutions - Peleng Roreng, Petrus (International Journal of Psychosocial Rehabilitation, 2020)
Organizational management is needed based on trust, especially in public sector organizations in Indonesia, especially professionals (auditors) who need professional skills. This study aims to analyze the influence of organizational culture on organizational performance in the audit function of government institutions. This research uses primary data (March-August, 2017 survey). The population is the representative of the Auditor's Functional Auditing Agency (BPK, BPKP, and Inspectorate) in South Sulawesi. A sample of 160 respondents was selected using a purposive random sampling method with a certain quota. Data were analyzed using SEM (Structural Equation Model) analysis. From the study of the results, it shows that organizational culture (X) for the Organizational Performance variable (Z) was 0.335. The path coefficient score of 0.335 shows the direct influence of organizational culture on organizational performance is 33.5%. A positive sign on the path coefficient of direct impact between organizational culture (X) on organizational performance (Z) shows that the better the organizational culture, the higher the organizational performance of functional audit institutions. It can conclude that organizational culture has a positive and significant influence on the performance of technical organizations of government audit institutions.